The mother act : a novel - Reimer, Heidi (Dutton, 2024)
"A clever and propulsive debut novel tracing the complicated relationship between a larger-than-life actress who refuses to abandon her career for motherhood, and the daughter she chooses to abandon instead, as they confront one another once and for all"--